Comparison of Malignant and Non-malignant Acquired Tracheoesophageal Fistulae Management Strategies and Outcomes - Munir Ahmad Baloch, Najam-ud-Din, Shahida Munir, Shazia Ismail, Nazir Ahmad, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the malignant and non-malignant acquired tracheoesophageal fistulae management strategies. Study design: Prospective study Place and duration of study: Bolan Medical College Teaching Hospital, Quetta from 1st January 2022 to 31st December 2022. Methodology: Sixty patients suffering from tracheoesophageal fistulae were enrolled. The patients were then divided into two groups where depending upon convenient sampling the first group was named as malignant while second was non-malignant group. The underlying etiology of each patient was recorded and assessments of clinical conditions were made through imaging and endoscopic techniques. The preoperative, intraoperative and stenting management strategies were applied on the enrolled cases. Single, double stenting was based on case to case. Results: The mean age of the cases with benign tracheoesophageal fistula was 10.5±1.2 years while those having malignant tracheoesophageal fistula was 51.2±6.5 years. There were total 20 cases of tracheoesophageal fistula with nonmalignant diagnosis while 40 cases with malignant tracheoesophageal fistula. Within the primary outcomes of the cases the preoperative mortality was higher in non-malignant cases than malignant while morbidity was much higher in the malignant cases with 35% in that presenting fistula recurrence. Practical Implication: Malignancy appeared to be the main cause of TEF in patients and their survival chances are also less. Conclusion: Stenting is best managing strategy in patients with improved survival rate malignant as well as non-malignant cases. Keywords: Malignancy, Fistula, Esophagus, Ventilator, Stenting